Hypnotic midday movie the art of Simon Hanselmann - Hanselmann, Simon 1981- (The Mansion Press, 2023)
"Discover "Hypnotic Midday Movie: The Art of Simon Hanselmann," the first artbook from internationally renowned artist Simon Hanselmann that showcases his most beautiful paintings featuring his beloved characters Megg Mogg & Owl. This artbook captures the very essence of Simon Hanselmann's sensibility: a disenchanted view of the world imbued with melancholy and gentleness despite the obvious pains of life. All the paintings are commented on by Simon Hanselmann himself!" -- Publisher
Rückseite: "A compilation of drawings, paintings and photographs published by The Mansion Press"
Keywords: Hanselmann, Simon -- 1981-; Comic books, strips, etc; Witches; Cats; Graphic novels; Humorous comics; Illustrated works; Biographies; Bildband